2018
DOI: 10.1590/1518-8345.2550.3022
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome and shift work among the nursing staff

Abstract: Objective:to analyze the factors associated with Burnout Syndrome among nursing workers according to work shift. Method:cross-sectional study addressing a representative sample of 502 nursing workers from a philanthropic hospital facility. Data were collected using a characterization instrument, the Maslach Burnout Inventory - Human Service Survey and the Demand-Control-Support Questionnaire. Data were analyzed using descriptive statistics and multiple binary logistic regression. Results:levels of Burnout Synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
2
26

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 45 publications
7
86
2
26
Order By: Relevance
“…Regarding the labour block, dissatisfaction with the current occupation, aggression in the work environment, absence of rest breaks, precarious technical resources and equipment, and night shifts were associated with BS. All variables mentioned are related to BS, according to the literature [32][33][34][35][36]. There is a paradox about the ideals and the reality of PHC in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the labour block, dissatisfaction with the current occupation, aggression in the work environment, absence of rest breaks, precarious technical resources and equipment, and night shifts were associated with BS. All variables mentioned are related to BS, according to the literature [32][33][34][35][36]. There is a paradox about the ideals and the reality of PHC in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Regarding marital status, 64.8% of workers lived with a partner, a condition frequently observed in studies involving health professionals, with similar values, 12,13 or older. 14,15 This result may be associated with the participants' mean age.…”
Section: Independent Variables Regression Coefficients Pmentioning
confidence: 88%
“…16 Physical activity may decrease symptoms of anxiety and depression in the nursing staff. 17 This study included several professional categories working in the WHML, which represented a differential concerning research in the area, which often involves nursing teams, 14,18 and teams composed of nursing staff and doctors. 12 The option to include different categories of performance in the hospital can contribute to a better understanding of workers' health in this environment.…”
Section: Job Satisfaction Quality Of Lifementioning
confidence: 99%
“…The reversal of the sleep and wake cycles significantly distorts the healthcare workers' endogenous circadian rhythms, which results in a range of adverse consequences impacting various domains of functioning [4,5]. Several studies have identified night shift work as an important occupational hazard with short-term and long-term adverse effects on nurses [5][6][7][8][9][10][11][12]. In the short term, it has been found to lead to the development of physical and mental symptoms, such as burnout and exhaustion, poor quality of life, eating disorders and sleep disorders, including shift work sleep disorder [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified night shift work as an important occupational hazard with short-term and long-term adverse effects on nurses [5][6][7][8][9][10][11][12]. In the short term, it has been found to lead to the development of physical and mental symptoms, such as burnout and exhaustion, poor quality of life, eating disorders and sleep disorders, including shift work sleep disorder [6,7,8,9]. In the long term, night shift work increases the risk of nurses becoming obese and developing impaired glucose tolerance, ischemic heart disease and cancer [10,11,12].…”
Section: Introductionmentioning
confidence: 99%